Belajar Bahasa Arab Berbasis Android - Naufal AL Qadri, Ahmad; Pawelloi, A.Irmayani (Jurnal Sintaks Logika, 2024)
The utilization of Arabic language learning Android application technology in education has not been optimal by educators and students. The study aims to design Arabic language learning applications for early childhood students. Using qualitative methods based on whitebox testing and blackbox testing using laptop hardware, smartphones, and Windows 11 software, Dart Framwork Flutter, Xampp, and MySQL the results of the application learning design make it easier for teachers and early learners to understand Arabic and carry out the teaching and learning process in the classroom properly.